PENGARUH MODEL PEMBELAJARAN SCRAMBLE BERBANTUAN MEDIA QUESTION CARD TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD - Alya Alifiana, Nafa; Suyanti; Nur Antika Eky Hastuti, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science education in elementary schools is currently facing challenges, primarily due to low student achievement. The causes include a teaching process that still relies heavily on lectures and rote memorization, as well as a lack of variety in instructional models and the use of educational media. These conditions result in students becoming passive, easily bored, and struggling to understand concepts in natural and social sciences. Therefore, there is a need for an innovative teaching approach that promotes student engagement and understanding. This study aims to determine the effect of the Scramble learning model assisted by Question Card media on the IPAS learning outcomes of fourth-grade elementary school students. The study uses a quantitative approach through an experimental method, specifically a Quasi-Experimental Design in the form of a Control Group Pretest-Posttest Design. The subjects were all 56 fourth-grade students at SDN Bangunsari 02 in Madiun Regency. The technique used was saturated sampling, in which the entire population served as the sample. Class VI/A was designated as the control class, while Class VI/B served as the experimental class. Data collection was conducted through multiple-choice tests in the form of pre-tests and post-tests on the subject of community economic activities. Data analysis involved tests of normality and homogeneity, followed by hypothesis testing using a Paired Samples T-Test with the assistance of SPSS software. The results of the study showed that the application of the Scramble learning model assisted by Question Card media had a positive effect on improving students’ IPAS learning outcomes. This learning model can increase student engagement, motivation, and understanding of concepts in learning activities that are collaborative, interactive, and enjoyable. Therefore, the Scramble learning model assisted by Question Card media can be an effective alternative for improving student learning outcomes in elementary school IPAS lessons.